Systematic review and meta‐analysis of the impact of dosimetry to dysphagia and aspiration related structures. Issue 6 (24th January 2019) - Charters, Emma Kristen; Bogaardt, Hans; Freeman‐Sanderson, Amy L.; Ballard, Kirrie J.
Abstract: Background: Technological advances in radiotherapy have allowed investigations into new methods to spare healthy tissue in those treated for head and neck cancer. This systematic review with meta‐analysis demonstrates the effect that radiation has on swallowing. Methods: Selection and analysis of studies examining the effect of radiation to swallowing structures. A fixed effects meta‐analysis calculated the pooled proportions for select outcomes of dysphagia, common across many studies. Results: The majority of the papers found a correlation between radiation dose to the swallowing structures and dysphagia, however a meta‐analysis found the studies carried a significant degree of heterogeneity. The appraisal demonstrates the need for large‐scale studies using a randomized design and instrumental dysphagia assessments. Conclusions: Radiation dose to dysphagia and aspiration structures is correlated with incidence of dysphagia and aspiration. The variables in this population contribute to the heterogeneity within and cross studies and future studies should consider controlling for this.